Steps of Cutting to Improve Psychomotor Abilities for Early Children, Age Group 4-6 Years - Lukman Hamid (International Journal of Emerging Issues in Early Childhood Education, 2021)
Pshycomotor is a movement that only involves certain parts of the body that are carried out by small muscles. Therefore Pshycmotor movements do not really need energy, but require careful coordination and accuracy. Pshycomotor skills begin to develop after starting with very simple activities such as holding a pencil, holding a spoon, and stirring. Cutting is easy, but if it does not go through the proper steps, the results of the cut will not be as expected. Scissors is a continuation of the stages of paper tearing activities in early childhood, cutting activities intended to train the child's Pshycomotorics, especially training the fingers of the child with paper media and knobs with certain stages and patterns   Keywords: Cutting is Part of The Pshycomotoric Stages of Early Childhood